A submersible probe with in-line calibration and a symmetrical reference element for continuous direct nitrate concentration measurements. Issue 3 (19th January 2023) - Forrest, Tara; Cherubini, Thomas; Jeanneret, Stéphane; Zdrachek, Elena; Damala, Polyxeni; Bakker, Eric
Abstract : A new autonomous, pre-programmable nitrate ion-selective submersible probe with a drift correction protocol, in-line calibration and a new reference system gives direct access to concentration and not activity. Abstract : Current methods to monitor nitrate levels in freshwater systems are outdated because they require expensive equipment and manpower. Punctual sampling on the field or at a fixed measuring station is still the accepted monitoring procedure and fails to provide real-time estimation of nitrate levels. Continuous information is of crucial importance to evaluate the health of natural aquatic systems, which can strongly suffer from a nitrogen imbalance. We present here a nitrate-selective potentiometric probe to measure the analyte continuously without requiring maintenance or high-power consumption. Owing to a simple design where the sensors are located directly in contact with the sample, the need for constant pump usage is eliminated, requiring just 0.7 mW power per day instead of 184 mW per day and per pump. It is estimated that with this power consumption, the setup can easily run for more than 97 h on four simple Li-ion batteries. A simple in-line one-point calibration step was implemented to allow for drift correction. At the same time, a symmetrical design was used involving a second nitrate probe as a reference electrode placed in the calibrant compartment. This, combined with an in situ calibration step, allows one to quantify nitrate ion concentrations directly, instead of yielding activities. The dependence on ion activity was removed by using the analysed sample spiked with nitrate as the calibrant. This results in essentially the same activity coefficients and additionally reduces junction potentials to a fraction of a millivolt. In addition, a symmetrical reference element served to compensate for fluctuations caused by environmental factors (temperature, convection, etc. ) to achieve improved stability and signal reproducibility compared to a traditional Ag/AgCl based reference electrode. The final prototype was deployed in the Arve River in Geneva for 75 h without requiring any intervention. The nitrate levels measured using the symmetrical reference element over this period were estimated at 44.0 ± 3.5 M and agreed well with the values obtained with ion chromatography (38.2 ± 2.1 μM) used as the reference method. Thanks to a modular sensing head the potentiometric sensors can be easily exchanged, making it possible to quantify other types of analytes and leading the way to a new monitoring strategy.